Gut microbial ecology of lizards: insights into diversity in the wild, effects of captivity, variation across gut regions and transmission - Kevin D. Kohl; Antonio Brun; Melisa Magallanes; Joshua Brinkerhoff; Alejandro Laspiur; Juan Carlos Acosta; Enrique Caviedes‐Vidal; Seth R. Bordenstein (Molecular Ecology, 2017)
Animals maintain complex associations with a diverse microbiota living in their guts. Our understanding of the ecology of these associations is extremely limited in reptiles. Here, we report an in‐depth study into the microbial ecology of gut communities in three syntopic and viviparous lizard species (two omnivores: Liolaemus parvus and Liolaemus ruibali and an herbivore: Phymaturus williamsi ). Using 16S rRNA gene sequencing to inventory various bacterial communities, we elucidate four major findings: (i) closely related lizard species harbour distinct gut bacterial microbiota that remain distinguishable in captivity; a considerable portion of gut bacterial diversity (39.1%) in nature overlap with that found on plant material, (ii) captivity changes bacterial community composition, although host‐specific communities are retained, (iii) faecal samples are largely representative of the hindgut bacterial community and thus represent acceptable sources for nondestructive sampling, and (iv) lizards born in captivity and separated from their mothers within 24 h shared 34.3% of their gut bacterial diversity with their mothers, suggestive of maternal or environmental transmission. Each of these findings represents the first time such a topic has been investigated in lizard hosts. Taken together, our findings provide a foundation for comparative analyses of the faecal and gastrointestinal microbiota of reptile hosts.

Generation and application of monoclonal antibodies against Rift Valley fever virus nucleocapsid protein NP and glycoproteins Gn and Gc - Susanne Jäckel; Martin Eiden; Malte Dauber; Anne Balkema-Buschmann; Alejandro Brun; Martin H. Groschup (Archives of Virology, 2014)